Size effect in bearing strength of concrete cubes - Ince, R; Arici, E (Elsevier Sci Ltd, 2004)
Experiments on concrete structure members under local pressure indicated that the compressive strength of concrete at the bearing area is increased by the confinement effect provided by the enveloping concrete. Although design codes propose specific criteria to prevent bearing failure, they do not consider size effect which is an important phenomenon in the fracture mechanics of concrete/reinforced concrete. In this study, six series of concrete cube specimens with size range 1:4 were tested under concentrated load. Maximum loads obtained from the test results were analyzed by means of Bazant's size effect law (SEL) and the results were compared with test data existing in the literature. In conclusion, the observed size effect is in good agreement with SEL. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: concrete; bearing strength; size effect law